2019
DOI: 10.21037/jtd.2019.11.27
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on coagulation function before and after off-pump coronary artery bypass grafting

Abstract: Background: This study aims to explore the influence of off-pump coronary artery bypass grafting (OPCABG) on coagulation function and the effects of diabetes on coagulation function during OPCABG.Methods: Patients who met the inclusion and exclusion criteria were divided into two groups: diabetes mellitus (DM) and non-diabetes mellitus (NDM) groups. Thromboelastography (TEG) was tested at the following time points: T0, five days after aspirin and clopidogrel therapy, and before OPCABG; T1, returning to care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Aspirin is the main therapeutic drug for preventing graft occlusion after coronary artery bypass grafting (CABG) [ 15 17 ]. It has been shown to prevent graft failure in patients undergoing coronary artery bypass grafting and ischemic complications such as myocardial infarction and stroke [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin is the main therapeutic drug for preventing graft occlusion after coronary artery bypass grafting (CABG) [ 15 17 ]. It has been shown to prevent graft failure in patients undergoing coronary artery bypass grafting and ischemic complications such as myocardial infarction and stroke [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of TEG in T2DM compared the diabetes group with a healthy control group and only a few studies analyzed the correlation between hemostasis and glycemic profile and the type of therapy for diabetes. 7,12,16 Therefore, the current study aimed to detect hemostasis abnormalities in association with glycemic levels and type of therapy among patients with T2DM by using TEG.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] A study by Xie et al, 34 revealed a decrease in R-value among patients with gestational diabetes mellitus which was not observed in normal pregnancy. Wang et al, 16 also obtained a lower R-value in acute stress after surgery among patients with DM compared to non-DM. Hyperglycemic condition combined with hyperinsulinemia may activate the coagulation system by increasing the activation of TF, FVII, FVIII, and platelet.…”
Section: Normocoagulablementioning
confidence: 92%
See 1 more Smart Citation
“…[7,8] Notably, either TEG detected hyper brinolysis or brinolysis shutdown was related to poor prognosis in patients with trauma or severe diseases. [9][10][11][12] In patients with CHDs, modi ed TEG was applied to measure platelet reactivity [13,14] and coagulation function [15]. However, little is known about abnormal brinolysis in patients with CHDs.…”
Section: Introductionmentioning
confidence: 99%